2003
DOI: 10.1038/sj.tpj.6500147
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression in carbon tetrachloride-treated rat livers using a novel bioarray technology

Abstract: The present study successfully utilizes a new ADME Rat Expression Bioarray, containing 1040 metabolism-and toxicology-linked genes, to monitor gene expression from the livers of rats treated with carbon tetrachloride (CCl 4 ). Histopathological analysis, hierarchical clustering methods, and gene expression profiling are compared between the control and CCl 4 -treated animals. A total of 44 transcripts were found to be altered in response to the hepatotoxin, 19 of which were upregulated and 25 were downregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 85 publications
2
20
0
Order By: Relevance
“…With this in mind, we first wanted to investigate whether calcium had any effect on the machinery needed for NO production in a rat model of humoral hypercalcemia of malignancy. Therefore, we performed a high-quality, oligonucleotide microarray analysis on four samples of total RNA subsequently made into cDNA from cells treated with either 3.5 or 0.5 mM calcium (41). The microarray data showed that H-500 cells treated with 3.5 mM calcium for 18 h exhibited an upregulation of iNOS mRNA compared with those treated with 0.5 mM calcium (P Ͻ 0.05; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…With this in mind, we first wanted to investigate whether calcium had any effect on the machinery needed for NO production in a rat model of humoral hypercalcemia of malignancy. Therefore, we performed a high-quality, oligonucleotide microarray analysis on four samples of total RNA subsequently made into cDNA from cells treated with either 3.5 or 0.5 mM calcium (41). The microarray data showed that H-500 cells treated with 3.5 mM calcium for 18 h exhibited an upregulation of iNOS mRNA compared with those treated with 0.5 mM calcium (P Ͻ 0.05; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It is limited to the degree of visual differentiation that can be achieved by the pathologist and may be affected by diagnostic drift or microscope fatigue. Recently, the use of automated pathology systems to provide the morphologic assessment of the tissue has been investigated to supplement the visual examination by a pathologist Kriete and Boyce, 2003;Young et al, 2003). By using automated tissue scanning microscopes and computer programs designed to identify abnormal tissue morphology, the process of correlating gene expression data and morphologic data may be automated.…”
Section: Comparison Of Morphologic Observations Withmentioning
confidence: 99%
“…RNA was extracted by an established protocol (Trizol reagent) from livers harvested at various times from rats rats treated with carbon tetrachloride (CCl 4 ), a well-known toxic compound causing liver damage 2 . Details of these sets were explained in previous reports 3,4 . A portion of each liver was also fixed in formalin, embedded in paraffin, slided and stained with hematoxylin and eosin for histology and automated image analysis.…”
Section: Biochip Technologymentioning
confidence: 99%